Implementation of an Interactive Learning Approach to Improve Third-Grade Students’ Learning Concentration at SD Negeri 4 Sulahan - Ekayanti, Ni Wayan; Sueca, I Nengah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This community service activity was carried out at SD Negeri 4 Sulahan by involving teachers and third-grade students as the main participants. The purpose of this program is to improve students’ learning concentration through the implementation of an interactive learning approach using video-based media. The methods used include observation and the application of learning by presenting video media relevant to the lesson content. The results show that the use of video media can enhance students’ attention, engagement, and learning motivation. Students became more focused during the lessons, showed enthusiasm while watching the videos, and actively participated in discussions and question-and-answer sessions. Teachers also experienced positive benefits, as video media provided variety in delivering material and created a more engaging and less monotonous classroom atmosphere. The implementation of this interactive learning approach proved effective in helping students understand the material more easily while also improving their thinking and communication skills. Overall, this community service activity successfully achieved its objectives, namely creating an active and enjoyable learning process that enhances elementary students’ learning concentration. Video media has been proven to serve as an alternative solution and reference for teachers in developing creative learning strategies that align with students’ characteristics.